PENGARUH TUI NA MASSAGE TERHADAP PICKY EATER PADA BALITA USIA 1 s.d 5 TAHUN DI BPM LILIS SURYAWATI JOMBANG - Lusianah Meinawati (Jurnal Insan Cendekia, 2021)
Introduction: Feeding difficulties in children are at high risk of becoming malnourished with age. Parents overcome children's feeding difficulties by giving them a multivitamin without paying attention to the cause. Recently it has been developed from a baby massage technique, namely the Tui Na massage. Objective: To analyze the effect of Tui Na massage on picky eaters. Purpose: Analyzing the effect of Tui Na massage on picky eaters. Method: Quasi experimental research design design. In this study, the experimental group was treated by giving tui na massage and for the control group by giving a multivitamin. The population of this study were all children under five in the working area of ​​the practicing midwife, Lilis Suryawati, totaling 286 children under five. Samples were taken by consecutive sampling method and obtained a total sample size of 50 respondents with a ratio of 1: 1 where the Tuina massage group was 25 people, and the group that was given multivitamins was 25 people. Result: Based on the results of the Wilcoxon statistical test, the p-Value is 0,000. From the p-value of 0.000 (<0.005), it shows that there is an effect of Tui Na massage on increasing appetite for children aged 1 to 5 years. Conclusion: Giving Tui Na massage to toddlers aged 1 to 5 years is more effective in overcoming feeding difficulties than giving multivitamins with a p-value (p = 0.000). Discuss: Parents, especially mothers, can apply Tui Na massage to their toddlers in order to avoid eating difficulties, and toddlers can grow and develop optimally. Key Word: Tui Na Massage, Picky Eater, Toddler